Maternal-fetal outcomes of exercise applied in rats with mild hyperglycemia after embryonic implantation - Soares, Thaigra S. [UNESP]; Moraes-Souza, Rafaianne Q. [UNESP]; Carneiro, Thalita B.; Araujo-Silva, Vanessa C.; Schavinski, Aline Z.; Gratão, Thamires B.; Damasceno, Débora C. [UNESP]; Volpato, Gustavo T. (Wiley, 2021)
Background: Exercise is commonly recommended to control hyperglycemia, including during pregnancy. We conducted this study to understand the potential benefits and risks of exercise during pregnancy of women with diabetes. Specifically, we evaluated the effects of swimming on a diabetic rat during pregnancy and assayed maternal-fetal parameters. Methods: Diabetes was induced in the female newborn from Wistar rats by the streptozotocin administration on first postnatal day. At 110 days of life, after confirm mild symptoms of diabetes, the rats were mated and randomly distributed into four experimental groups (minimum of 13 animals/group): Control (C)—nondiabetic animals without swimming; Control and Exercise (CEx)—nondiabetic animals submitted to swimming; Mild Diabetic (MD)—diabetic animals without swimming; Mild Diabetic and Exercise (MDEx)—diabetic animals submitted to swimming. The swimming program was performed from day 7 to 21 of pregnancy. Maternal parameters were evaluated during the pregnancy period. On day 21 of pregnancy, the rats were sacrificed and maternal and fetal parameters analyzed. Results: There are no alterations in body weight, food consumption, water intake, and reproductive outcomes among the groups. The swimming program did not normalize maternal glycemia and other biochemical biomarkers. The diabetes and exercise combination increased organ weight. The fetuses born to these exercising diabetic rats had reduced fetal weight and increased skeletal anomalies (mainly incomplete ossification of sternebra). Conclusion: The intense swimming exercise imposed on female rats during pregnancy impaired maternal metabolic repercussions, contributing to intrauterine growth restriction and fetal skeletal anomalies.
Keywords: diabetes; lipid profile; malformation; physical exercise; pregnancy